Whole-Genome Sequencing and Phylogenetic Analysis of Francisella tularensis Vaccine Strain 15 NIIEG - E. A. Naryshkina; Ya. M. Krasnov; Zh. V. Alhova; D. V. Badanin; A. V. Osin; O. Yu. Lyashova; L. V. Sayapina; V. P. Bondarev; V. A. Merkulov; Yu. V. Olefir; V. V. Kutyrev (Проблемы особо опасных инфекций, 2020)
Objective of the study was to conduct whole-genome sequencing of the vaccine strain Francisella tularensis 15 NIIEG and determine, based on the results, its phylogenetic relationships and the genetic organization features.Materials and methods. Whole-genome sequencing of F. tularensis 15 NIIEG strain was performed on Ion PGM (Ion Torrent, USA) and MinIon (Oxford Nanopore Technologies, UK) platforms. Alignment of readings obtained to the whole-genome of F. tularensis subsp. holarctica LVS (CP009694, USA, 2015) was performed using the software package DNASTAR Lasergene 15.3. Hybrid assembly of reads into contigs was performed by means of Unicycler v. 0.4.4, using data obtained by semiconductor sequencing technology (Ion PGM) and nanopore sequencing (MinIon). Phylogenetic analysis was performed on the basis of single nucleotide polymorphism (SNPs) data located in the core part of F. tularensis genome. Maximum parsimony algorithm was used to construct a dendrogram using the obtained data of common SNP-matrix.Results and discussion. The close relations of F. tularensis 15 NIIEG strain with F. tularensis LVS vaccine strain used in the countries of Western Europe and North America was confirmed. Searching for common single mutations characteristic of F. tularensis 15 vaccine strains of NIIEG and LVS, permitted to find 5 unique SNPs that distinguish them from all other 228 F. tularensis strains used in the comparison. Comparative genomic analysis ofF. tularensis 15 NIIEG vaccine strain and virulent strains revealed in its structure two extensive 526 bp deletions (genes pilA and pilE) and 1480 bp (genes encoding lipoprotein). Similar deletions are also present in the genome of the F. tularensis LVS vaccine strain.